2012
DOI: 10.1093/aobpla/pls025
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic capacity is negatively correlated with the concentration of leaf phenolic compounds across a range of different species

Abstract: This study reveals a negative relationship between leaf phenolic compounds and photosynthetic Amax among different plant species. This indicates a functional integration among carbon gain and the concentration of leaf phenolic compounds that reflects the trade-off between growth and defence/protection demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 38 publications
3
20
0
2
Order By: Relevance
“…Under CA stress, PN was negatively correlated with the concentration, which was in accordance with Mersie and Singh (1993) and Sumbele et al (2012). Under the low and moderate concentrations of CA, PN, Ci, E, and gs in the seedlings of R. delavayi were significantly lower than that of CK; however, gs, E, WUE, and Ls showed no significant difference between the low and moderate concentrations of CA (Fig.…”
Section: Photosynthetic Characteristicssupporting
confidence: 79%
“…Under CA stress, PN was negatively correlated with the concentration, which was in accordance with Mersie and Singh (1993) and Sumbele et al (2012). Under the low and moderate concentrations of CA, PN, Ci, E, and gs in the seedlings of R. delavayi were significantly lower than that of CK; however, gs, E, WUE, and Ls showed no significant difference between the low and moderate concentrations of CA (Fig.…”
Section: Photosynthetic Characteristicssupporting
confidence: 79%
“…5) is not yet known. Increased allocation of carbon to UV-absorbing compounds may have negative consequences for photosynthesis (Sumbele et al, 2012) such that reducing UV protection during times of the day when solar UV levels are low could enhance daily carbon gain. In comparison to plants that maintain high UV sunscreen protection throughout the day, plants with horizontal leaves that exhibit diurnal changes in epidermal UV transmittance will experience increased UV exposure to the underlying mesophyll both early and late in the day but not at midday (Fig.…”
Section: Temporal Dynamics Of Uv Protectionmentioning
confidence: 99%
“…Decline in chlorophyll contents was highly associated with production of phenolic compounds (Table 5). Recently, Sumbele et al (2012) reported with 49 plant species of Greece and Australia that photosynthetic capacity was negatively associated with leaf phenolic contents. Wheat allelochemical compounds might have inhibited chlorophyll content in canary grass seedlings either by interfering with the biosynthesis of photosynthetic pigments or by enhancing their degradation by inducing oxidative stress and generation of reactive oxygen species or both.…”
Section: Discussionmentioning
confidence: 99%